New Avenues for Organic Redox Materials as Sustainable Lithium-ion Battery Cathodes - Gupta, Deepak; Gupta, Shilpa Jain; Vlad, Alexandru (Organic Materials, 2023)
As the demand for electrification of means of transportation and storage of electrical energy for later use is skyrocketing, rechargeable Li-ion batteries (LIBs) are at the heart of this revolution. Acknowledging the carbon footprints, environmental concerns and cost of the commercial cathode materials, this is the high time to advocate sustainable alternatives. This review aims at establishing the potential of organic redox-active molecules as a burgeoning class of sustainable solid cathode materials for LIBs. The materials are classified according to their structural features (molecules, metallo-organic complexes, and organic/metal–organic frameworks) and electrochemical performance to lay emphasis on practical applications and bottlenecks in commercialization. However, these materials are still in early stages of development, and new frontiers have been explored in the last five years.
Keywords: batteries; Li-ion batteries; organic materials; energy storage